2021
DOI: 10.1128/jvi.00699-21
|View full text |Cite
|
Sign up to set email alerts
|

STING Ligand-Mediated Priming of Functional CD8+T Cells Specific for HIV-1-Protective Epitopes from Naive T Cells

Abstract: Functional HIV-1-specific CD8 + T-cells primed from naïve T-cells are expected to act as effector T-cells in a ‘‘shock and kill’’ therapeutic strategy for an HIV-1 cure since less functional HIV-1-specific CD8 + T-cells are elicited from memory T-cells in HIV-1-infected individuals on cART. CD8 + T-cells specific for HIV-1 conserved and protective epitopes are candidates of such T-cells. We here investigated the priming with STING ligand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The protein level of HLA alleles on HIV-1 infected cells is a critical factor for T cell priming. 52 Because the expressions of HLA-A and HLA-B were higher than that of HLA-C, 53 , 54 , 55 even in HIV-1-infected cells, HLA-A- or HLA-B-restricted T cells may be primed more immediately and effectively after exposure to HIV-1 than HLA-C-restricted T cells. Indeed, the number of reported HLA-C-restricted HIV-1 epitopes is much smaller than that of HLA-A-restricted or HLA-C-restricted epitopes (LANL-HSD: www.hiv.lanl.gov ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein level of HLA alleles on HIV-1 infected cells is a critical factor for T cell priming. 52 Because the expressions of HLA-A and HLA-B were higher than that of HLA-C, 53 , 54 , 55 even in HIV-1-infected cells, HLA-A- or HLA-B-restricted T cells may be primed more immediately and effectively after exposure to HIV-1 than HLA-C-restricted T cells. Indeed, the number of reported HLA-C-restricted HIV-1 epitopes is much smaller than that of HLA-A-restricted or HLA-C-restricted epitopes (LANL-HSD: www.hiv.lanl.gov ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study of HIV-1-specific T cell priming from naive T cells demonstrated that HLA-B-restricted T cells were primed from naive T cells whereas HLA-C-restricted ones were not in the same individuals. 55 Other studies demonstrated that the peptide binding affinity was positively associated with the frequency of T cell responses in HIV-1-infected individuals 56 and that peptide stability may mediate T cell immunodominance. 57 These studies suggest that HIV-1-specific T cells are preferentially induced after exposure to HIV-1 in HESN individuals if the binding affinity and/or stability of the epitope peptide is high.…”
Section: Discussionmentioning
confidence: 99%